1998
DOI: 10.1021/ie970118x
|View full text |Cite
|
Sign up to set email alerts
|

Jet Mixing of Liquids in Long Horizontal Cylindrical Tanks

Abstract: Large storage tanks may require mixing to achieve homogeneity of contents for several reasons:  prior to sampling for mass balance purposes, for blending in reagents, for suspending settled solids for removal, or for use as a feed tank to a process. At Oak Ridge National Laboratory, mixed waste evaporator concentrates are stored in ∼190-m3 (50 000-gal) horizontal tanks, about 3.7 m (12 ft) in diameter and 18 m (60 ft) in length. This tank configuration has the advantage of permitting transport by truck and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…The equilibrium temperature, T , can be easily calculated and was found to be 302:7295 K. The mixing time was measured according to the above criterion which means that the temperature at any point inside the tank should be in the range of 300 ± 0:136475 K. The numerical model can also be used to solve for concentration. Most experimental studies including those of Fossett and Prosser (1949), Fox and Gex (1956), Lane and Rice (1982) and Perona et al (1998) quantiÿed mixing by taking experimental readings of the measured variable at a small number of predetermined locations. These locations need not coincide with those where the mixing time is longest.…”
Section: Mathematical Formulation and The Numerical Modelmentioning
confidence: 99%
“…The equilibrium temperature, T , can be easily calculated and was found to be 302:7295 K. The mixing time was measured according to the above criterion which means that the temperature at any point inside the tank should be in the range of 300 ± 0:136475 K. The numerical model can also be used to solve for concentration. Most experimental studies including those of Fossett and Prosser (1949), Fox and Gex (1956), Lane and Rice (1982) and Perona et al (1998) quantiÿed mixing by taking experimental readings of the measured variable at a small number of predetermined locations. These locations need not coincide with those where the mixing time is longest.…”
Section: Mathematical Formulation and The Numerical Modelmentioning
confidence: 99%
“…It was reported that alternating jets gives 15% less mixing time at the same power input as compared with steady jets. Perona et al (1998) studied the performance of jet mixers in long horizontal tanks. Considerable literature and measurements on jet mixing in tanks are available.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the surrounding fluid is entrained by jet within L/d of 400 (Harnby et al, 1997;Perona et al, 1998;Wasewar and Sarathi, 2008). These results ensured that the jets can entrain the external liquid and generate the circulation inside the tanks.…”
Section: Effect Of Jet Nozzle Angle On Mixing Timementioning
confidence: 92%